2012
DOI: 10.1155/2012/861296
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C-Based Evaluation of Kidney Function of HIV-Infected Children in Benin City, Southern Nigeria

Abstract: Background. Human immunodeficiency virus (HIV) is now a confirmed risk factor for kidney disease with an increased burden in persons of African descent. Method. We measured the serum cystatin C levels of 205 ART-naive, HIV-infected children by an ELISA technique and compared them with the levels of apparently healthy children. Result. The mean ± SD serum cystatin C level of children with HIV infection was 1.01 ± 0.44 mg/L, significantly higher than the mean value in the control group, that is, 0.72 ± 0.20 mg/L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 28 publications
0
17
3
Order By: Relevance
“…The very different clinical and immunologic situation in the 2 Nigerian cohorts (low CD4 counts, naive status, black ethnicity, malnutrition and advanced HIV disease) compared with our cohort makes comparisons difficult. Mean cystatin C levels (0.87 mg/L) in our study are lower than those reported by other studies in pediatric (1.01 mg/L) 16 and adult HIV cohorts (1.03 mg/L) 38 ; most importantly, no differences in cystatin C values were found with healthy controls, as opposed to previous studies. 16,17,39,40 The optimal immunologic and clinical situation in our cohort, including renal function, probably explains these findings.…”
Section: Discussioncontrasting
confidence: 94%
See 4 more Smart Citations
“…The very different clinical and immunologic situation in the 2 Nigerian cohorts (low CD4 counts, naive status, black ethnicity, malnutrition and advanced HIV disease) compared with our cohort makes comparisons difficult. Mean cystatin C levels (0.87 mg/L) in our study are lower than those reported by other studies in pediatric (1.01 mg/L) 16 and adult HIV cohorts (1.03 mg/L) 38 ; most importantly, no differences in cystatin C values were found with healthy controls, as opposed to previous studies. 16,17,39,40 The optimal immunologic and clinical situation in our cohort, including renal function, probably explains these findings.…”
Section: Discussioncontrasting
confidence: 94%
“…Mean cystatin C levels (0.87 mg/L) in our study are lower than those reported by other studies in pediatric (1.01 mg/L) 16 and adult HIV cohorts (1.03 mg/L) 38 ; most importantly, no differences in cystatin C values were found with healthy controls, as opposed to previous studies. 16,17,39,40 The optimal immunologic and clinical situation in our cohort, including renal function, probably explains these findings. Only 2 of 83 patients showed estimated GFR <90 and none <60 mL/min/1.73m 2 in our study; of note, both girls were receiving HAART regimens including tenofovir.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations